FORMATION OF WORLDVIEW IN THE CONTEXT OF THE HISTORICAL FACTOR UNDER CONDITIONS OF SOCIOCULTURAL TRANSFORMATION (Uzbekistan Open Conference, 2025)
The article examines the process of the formation of both individual and collective worldviews under the influence of the historical factor in an era of intense sociocultural transformations. The author argues that history functions not merely as a collection of past events but as an active constructor of meanings, values, and identities.